OTONOMI DAERAH: KAJIAN KESIAPAN DUNIA USAHA DAN BIROKRASI - Ihwan Susila (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
Decentralization is the reflection of economic and politic reformation. The politic change in developing countries in the last decade shows the tendency that local government has the authority to public service in the local society. Due to technology change and integration in the global market, it is a big demand for the government to control the politic and economic system in the country. The regional autonomy has two different effects. The regional autonomy, however gives the opportunity to their districts to grow and develop their own districts. On the contrary, the regional autonomy can be worse. This occurs due to the lack of preparation of the district to apply the policy. The key to minimize or eliminate the problem is by enhancing the quality of human resources. Preparation of business and bureaucracy to face the regional autonomy will be discussed.